2019
DOI: 10.1371/journal.pone.0223571
|View full text |Cite
|
Sign up to set email alerts
|

A survey of public attitudes toward uterus transplantation, surrogacy, and adoption in Japan

Abstract: This study aimed to evaluate the attitudes of male and female members of the public toward uterus transplantation (UTx), surrogacy, and adoption in Japan via a web-based survey. One thousand six hundred participants were recruited with equal segregation of age (20s, 30s, 40s, and 50s) and gender. We assessed the association between ethical view and gender, age, infertility, and the knowledge level of UTx, using a questionnaire. The findings were as follows. First, 36.5% and 31.0% of respondents agreed that UTx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…İran ve Japonya'da yapılan çalışmalarda, kadın ve erkeklerin yaklaşık olarak aynı oranda, Türkiye, Ürdün, Kanada ve Japonya'da yapılan çalışmalarda, erkeklerin kadınlara göre taşıyıcı anneliğe daha olumlu yaklaşım sergilediği tespit edilmiştir. [10][11][12][13][14][15][16] Ahmadi ve Bambad'ın çalışmasında, taşıyıcı annelik, sperm yumurta bağışına yaklaşım ve cinsiyet arasında anlamlı bir ilişki bulunmamıştır. 17 kullanılan ölçme yöntemlerinden, bölgesel ya da örneklem farklılıklarından kaynaklandığı düşünülebilir.…”
Section: Discussionunclassified
“…İran ve Japonya'da yapılan çalışmalarda, kadın ve erkeklerin yaklaşık olarak aynı oranda, Türkiye, Ürdün, Kanada ve Japonya'da yapılan çalışmalarda, erkeklerin kadınlara göre taşıyıcı anneliğe daha olumlu yaklaşım sergilediği tespit edilmiştir. [10][11][12][13][14][15][16] Ahmadi ve Bambad'ın çalışmasında, taşıyıcı annelik, sperm yumurta bağışına yaklaşım ve cinsiyet arasında anlamlı bir ilişki bulunmamıştır. 17 kullanılan ölçme yöntemlerinden, bölgesel ya da örneklem farklılıklarından kaynaklandığı düşünülebilir.…”
Section: Discussionunclassified
“…Alternatives to UTx are childlessness, adoption or gestational surrogacy. A survey in Japan indicated that the lay public would choose UTx (34.4%), gestational surrogacy (31.9%) or adoption (40.3%) if there were AUFI (Nakazawa et al, 2019). Adoption is a long and difficult process.…”
Section: Ethical Questionsmentioning
confidence: 99%
“…A questionnaire survey conducted by a group at Tokyo University in 2017 showed similar results. 39 However, it cannot be said that the technology of UTx is fully known to Japanese society, and it is necessary for medical personnel to provide accurate information, including the advantages and disadvantages of UTx, to Japanese society. Further investigations to establish the societal need for UTx in Japan should be carried out.…”
Section: Awareness Survey Of Attitudes Toward Utx In Reproductive-aged Japanese Womenmentioning
confidence: 99%